A formação docente leitora no curso de pedagogia - Alencar, Daniela Deyse Silva de (Universidade Federal Rural do Semi-Árido, 2020)
It is important that the teacher, especially the Pedagogue, to have initial training that collaborates to make him didatic as future reader trainer in Basic Education. Our objective research, in a general way, analyzes how the reading teacher education of undergraduate students in a public university in the municipality of Mossoró/RN takes place to act as future teachers who train readers, and the specifics objectives are: analyze what the document that guides the Pedagogy Course on reading training points out; identify the conceptions of the student/future teacher about their reading training and identify the teachers' conceptions about the importance of reading training in the Pedagogy Course. The investigation approach is qualitative, characterized as a study case. For this, we used the document that governs the Course in mention and the data collected from the research subjects through interviews and questionnaires. In addition, it was necessary to understand and use theoretical studies about teacher training and knowledge (TARDIF, 2013; PIMENTA, 2012) and from the reading (FREIRE, 2011; MARTINS, 2006). In reference of regard to reader training and literature, we based ourselves in Azevedo (2004), Lajolo (1993) and Pontes (2012). That said, it was possible to realize a analysis from the triangulation of the data obtained through the document (Pedagogical Course Project - PCP), through field research from the application of the questionnaire with the students and the interview with the teachers of the Pedagogy Course and with that, identify which practices starting with the literary reading is a relevant strategy for the reading formation in context of teacher training. We also verified that this document highlights that necessity to work more on the reading training of students and amplify the number of compulsory subjects in its curricular component that deals with reader training. We found that students consider literary reading as a reading modality that provides significant experiences in the context of teacher education. The teachers defend the need for the university and everyone involved in this process to develop more teaching, research and extension projects that encourage the practice of literary reading as a relevant modality to train reader educators. With all of this, we conclude that despite the existence of some difficulties, the Pedagogy Course, the locus of the research, contributes to the reading training of the respective students
Keywords: Formação docente; Formação leitora; Leitura; Literatura; Teacher training; Reading training; Reading; Literature; MULTIDISCIPLINAR::ENSINO